The neapolitan camorra: Crime and politics in post-war Naples (1950-92) - Allum, Felia Skyle (2000)
This thesis was submitted for the degree of Doctor of Philosophy and awarded by Brunel University, 15/05/2000.In the post-war period, Italy has been plagued by different forms of organised crime (such as the Sicilian Mafia, the Neapolitan Camorra, the Calabrian 'Ndrangheta and the Pugliese Sacra Corona Unita) which have managed in their individual ways to infiltrate both the State (in the form of political parties and local administrations) and society (businesses, cultural and voluntary organisations). In Campania, until 1991, the relationship between the Camorra and the local political elite (based on the exchange of votes for state contracts and protection) was tacitly accepted by the population and could not be studied by political scientists due to the lack of reliable source material. In 1991, a law was introduced which gave generous remission of sentences to criminals who became state-witness. Many members of the Camorra revealed important aspects of criminal, economic and political activities in Campania. This new material permitted a reexamination of the Camorra. This thesis on the Camorra hopes to fill a gap in the study of the relationship between politics and criminal organisations which so far has concentrated on the Sicilian Mafia. Part One is a general introduction and presents the theoretical model and methods adopted. The documentation available allowed us to adopt an agency-structure approach derived from Giddens's structuration theory (1984). This was complemented by Easton's systems analysis (1965) to understand the wider, macro-environment. We elaborated an 'interaction model' to analyse the changing nature of the Camorra's activities: from a simple social-criminal practice in the 1930s to a dynamic and secret cartel enacting a political-criminal practice in the 1980s. To test this model we applied it to case-studies of criminals using original judicial documents. In Part Two we look at the possible motives of people who join the Camorra. We analysed the agent's internal and external structure in both decades and concluded that the macro-environment as an influencing factor had changed more than the individual-agent. Part Three examines the lives of camorristi in the 1950s and 1980s in order to determine how far their criminal practice has been transformed. Part Four investigates the wider picture of system-interaction between the Camorra's social subsystem and the political system. Focussing on the relationship between camorristi and the political elite in the 1950s and 1980s we highlight the radical changes that occurred. This thesis presents a theoretical discussion of how to study organised crime and social behaviour in general and at the same time a detailed empirical study, in particular of the political role of a criminal organisation in a concrete historical situation, that of Naples over the last forty years.Brunel University; Italian Governmen